Effect of fermented gambir (Uncaria gambir) leaves on broiler performance and blood lipids - TUTI WIDJASTUTI; ATHAYA FAADHILAH; LOVITA ADRIANI (Asian Journal of Agriculture, 2025)
Abstract. Widjastuti T, Faadhilah A, Adriani L. 2025. Effect of fermented gambir (Uncaria gambir) leaves on broiler performance and blood lipids. Asian J Agric 9: 615-622. Increasing broiler chicken productivity must be supported by proper management during rearing. Efforts to maintain production efficiency with potential alternatives to replace antibiotic growth promoters (AGP) include gambir leaves (Uncaria gambir). Fermented gambir leaves aim to improve performance and reduce blood lipid levels in broiler chickens, serving as an alternative ingredient to replace antibiotic growth promoters. The leaves are fermented with Lactobacillus plantarum at 1.5% and Rhizopus oligosporus at 1%. The study used a completely randomized design (CRD) with five treatments and four replicates. R0: 100% basal diet; R1: 100% basal diet + 0.5% fermented gambir leaf product; R2: 100% basal diet + 1% gambir leaf fermentation product; R3: 100% basal diet + 1.5% fermented gambir leaf product; R4: 100% basal diet + 2% gambir leaf fermentation product. Parameters measured included performance, blood, and meat lipid levels. Results showed significant differences (P<0.05) among treatments R1-R4 compared to R0, indicating increased body weight gain (R1=2393 g) and decreased cholesterol (R1=115 mg/dL), triglyceride (R1 = 49 mg/dL), and fat levels in blood and meat. Based on these findings, adding 1% fermented gambir leaves to the basal diet can improve broiler performance while reducing lipid content in blood plasma and meat. Using 0.5% to 1% gambir leaf fermentation in feed is recommended as a feed additive to replace AGP.